A Pragmatic Benchmarking Study of an Evidence-Based Personalised Approach in 1938 Adolescents with High-Risk Idiopathic Scoliosis - Stefano Negrini (MDPI AG, 2021)
Combining evidence-based medicine and shared decision making, current guidelines support an evidence-based personalised approach (EBPA) for idiopathic scoliosis in adolescents (AIS). EBPA is considered important for adolescents’ compliance, which is particularly difficult in AIS. Benchmarking to existing Randomised Controlled Trials (RCTs) as paradigms of single treatments, we aimed to check the effectiveness and burden of care of an EBPA in high-risk AIS. This study’s design features a retrospective observation of a prospective database including 25,361 spinal deformity patients < 18 years of age. Participants consisted of 1938 AIS, 11–45° Cobb, Risser stage 0–2, who were studied until the end of growth. EBPA included therapies classified for burdensomeness according to current guidelines. Using the same inclusion criteria of the RCTs on exercises, plastic, and elastic bracing, out of the 1938 included, we benchmarked 590, 687, and 884 participants, respectively. We checked clinically significant results and burden of care, calculating Relative Risk of success (RR) and Number Needed to Treat (NNT) for efficacy (EA) and intent-to-treat analyses. At the end of growth, 19% of EBPA participants progressed, while 33% improved. EBPA showed 2.0 (1.7–2.5) and 2.9 (1.7–4.9) RR of success versus Weinstein and Coillard’s studies control groups, respectively. Benchmarked to plastic or elastic bracing, EBPA had 1.4 (1.2–1.5) and 1.7 (1.2–2.5) RR of success, respectively. The EBPA treatment burden was greater than RCTs in 48% of patients, and reduced for 24% and 42% versus plastic and elastic bracing, respectively. EBPA showed to be from 40% to 70% more effective than benchmarked individual treatments, with low NNT. The burden of treatment was frequently reduced, but it had to be increased even more frequently.